Dietrich Bonhoeffer, Prayerbook of the Bible, and the Reichsschrifttumskammer (RSK): Reassessing the Historical Record - Clark, David A. R. (Studies in Christian-Jewish Relations, 2022)
This article examines Geffrey B. Kelly’s argument that, in 1941, the Reichsschrifttumskammer (RSK) prohibited Bonhoeffer from publishing because the agency objected to the ostensibly pro-Jewish and anti-Nazi content of Prayerbook of the Bible: An Introduction to the Psalms. The primary sources show that Kelly’s claims are unsupported by the historical record, as there is no evidence that Prayerbook figured into the deliberations of the RSK. If Prayerbook has implications for post-Holocaust Jewish-Christian conversations, then these implications must be demonstrated with reference to the text itself and not by recourse to its supposed reception by Nazi authorities. Kelly’s account exemplifies a problematic tendency to interpret Bonhoeffer, in the context of Jewish-Christian relations, through a misleadingly heroic or hagiographical lens.